Genetic Dissection Uncovers Genome-Wide Marker-Trait Associations for Plant Growth, Yield, and Yield-Related Traits Under Varying Nitrogen Levels in Nested Synthetic Wheat Introgression Libraries - Sandhu, Nitika; Kaur, Amandeep; Sethi, Mehak; Kaur, Satinder; Varinderpal-Singh,; Sharma, Achla; Bentley, Alison R.; Barsby, Tina; Chhuneja, Parveen (Frontiers in Plant Science, 2021)
Nitrogen is one of the most important macronutrients for crop growth and metabolism. To identify marker-trait associations for complex NUE-related agronomic traits, field experiments were conducted on nested synthetic wheat introgression libraries at three nitrogen input levels across two seasons. The introgression libraries were genotyped using the 35K Axiom® Wheat Breeder’s Array and genetic diversity and population structure were examined. Significant phenotypic variation was observed across genotypes, treatments and their interactions across seasons for all the 22 traits measured. Significant positive correlations were observed among grain yield and yield attributing traits and root traits. Across seasons, a total of 233 marker-trait associations (MTAs) associated with fifteen traits of interest at differential levels of nitrogen (N0, N60 and N120) were detected using 9,474 genome-wide single nucleotide polymorphism (SNP) markers. Of these, 45 MTAs for 10 traits in the N0 treatment, 100 MTAs for 11 traits in the N60 treatment and 88 MTAs for 11 traits in the N120 treatment were detected. We identified putative candidate genes underlying the significant MTAs which were associated directly or indirectly with various biological processes, cellular component organization and molecular functions involving improved plant growth and grain yield. In addition, the top 10 lines based on N response and grain yield across seasons and treatments were identified. The identification and introgression of superior alleles/donors improving NUE while maintaining grain yield may open new avenues in designing next-generation nitrogen efficient high yielding wheat varieties.